Implementasi Evaluasi Kinerja Karyawan Pada PT. Pegadaian Unit Pelayanan Cabang (UPC) PADANG Panjang - Faisal Hadi; Dewi Manda Angraini; Rika Widianita; Santi Deswita (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2025)
This study aims to determine the implementation of employee performance evaluation at PT. Pegadaian Branch Service Unit (UPC) Padang Panjang. Performance evaluation is an important process in improving work effectiveness and ensuring the alignment between task implementation and the company's strategic objectives. This study focuses on five main aspects of performance evaluation, namely relevance, reliability, sensitivity, acceptability, and practicality. The research method used is qualitative research with a descriptive approach. Data were obtained through direct interviews with the management of PT. Pegadaian UPC Padang Panjang, observations of the performance evaluation process, and other supporting documentation. Data analysis was carried out through the stages of data reduction, data presentation. The results of the study indicate that the implementation of performance evaluation at PT. Pegadaian UPC Padang Panjang has been running well and effectively. The evaluation is relevant to the company's strategy, reliable because it is carried out transparently and trustworthy, sensitive in differentiating employee performance levels, acceptable because it is well received by all employees without causing conflict, and practical because it is carried out simply, efficiently, and easily understood. Performance evaluation also has a positive impact on increasing employee motivation, productivity, and work quality. Thus, it can be concluded that the performance evaluation system implemented by PT. Pegadaian UPC Padang Panjang has played a significant role in improving organizational effectiveness and supporting the sustainable achievement of the company's strategic goals.